PEMBERHENTIAN HAKIM MAHKAMAH KONSTITUSI OLEH DEWAN PERWAKILAN RAKYAT DITINJAU DARI SISTEM KETATANEGARAAN INDONESIA - Aura Silvanie; Erry Gusman; Nessa Fajriyana Farda (Ensiklopedia of Journal, 2023)
Abstract: The purpose of this research is to find out the constitutionality of dismissal of Constitutional Court judges by the House of Representatives. This research is a type of juridical normative legal research that uses an approach to legislation. The results of the study explain that the steps of the House of Representatives towards the Constitutional Court increasingly show an attitude of authoritarianism and legal defiance, because the actions is contradict the provisions of Article 24 paragraph (1) of the 1945 Constitution (1945 Constitution) which guarantees the existence of independent judicial power institutions. Also the actions taken outside the provisions of the norms of Article 23 of law number 24  of 2003 concerning the Constitutional Court Law. This action is not in line with the rule of law in Indonesia and has a potential  to  damage  and  disrupt  judicial  power  as  the  main stronghold of the rule of law.Keywords: Dismissal Judge, Constitutional Court, House of Representatives